Consent and Sexual Offenses Comparative Perspectives - Hoven, Elisa; Weigend, Thomas (Sexualität in Recht und Gesellschaft, 2022)
In sexual relations, consent makes the difference between pleasure and crime. Yet, due to the impact of personal, social, and cultural conditions on sexual interactions, defining the prerequisites of legally valid consent to sexual acts presents great challenges. This volume collects essays, national reports, and a comparative synopsis authored by experts from eleven jurisdictions. The broad spectrum of contributions provides policymakers and jurists interested in sexual crime with up-to-date information and legal argument. Elisa Hoven and Thomas Weigend are professors of criminal law at the universities of Leipzig and Cologne active in developing criminal policy. They have done extensive research in comparative criminal law. With contributions by Asst.-Prof. Dr. Baris Atladi; Dr. Gian Marco Caletti; Dr. Andrew Dyer, LL.B, LL.M; Prof. Aya Gruber, J.D.; Dr. Lyndon Harris, Barrister; Prof. Dr. Elisa Hoven; Prof. Dr. Wojciech Jasiński; Dr. Karolina Kremens; Prof. Dr. Kai Lindenberg; Dr. Sebastian Mayr; Dr. Hannah Quirk; Dr. Nora Scheidegger; Univ.-Prof. Dr. Kurt Schmoller; Dr. Linnea Wegerstad and Prof. Dr. Thomas Weigend.